2018
DOI: 10.1111/iju.13807
|View full text |Cite
|
Sign up to set email alerts
|

Tumor growth velocity: A modified tumor growth rate defining tumor progression during sorafenib treatment in patients with metastatic renal cell carcinoma

Abstract: Objectives To investigate the role of tumor growth velocity in defining tumor progression in metastatic renal cell carcinoma patients treated with the vascular endothelial growth factor tyrosine kinase inhibitor, sorafenib. Methods A modified calculation for tumor growth velocity was introduced to evaluate the tumor growth velocity, before and after sorafenib withdrawal. Known prognostic factors together with tumor growth velocity before drug withdrawal and tumor growth velocity after drug withdrawal were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The introduction of tyrosine kinase inhibitors and immunotherapies has remarkably improved the survival of mRCC patients. [1][2][3][4][5][6][7][8][9][10][11][12] Randomized studies suggested the efficacy of first-line nivolumab plus ipilimumab in patients belonging to the intermediate-and poor-risk groups of the IMDC. [13][14][15] However, the efficacy and safety of the first-line nivolumab plus ipilimumab for mRCC patients need to be validated in actual practice, 14 and CheckMate 214 trial only enrolled a limited number of Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of tyrosine kinase inhibitors and immunotherapies has remarkably improved the survival of mRCC patients. [1][2][3][4][5][6][7][8][9][10][11][12] Randomized studies suggested the efficacy of first-line nivolumab plus ipilimumab in patients belonging to the intermediate-and poor-risk groups of the IMDC. [13][14][15] However, the efficacy and safety of the first-line nivolumab plus ipilimumab for mRCC patients need to be validated in actual practice, 14 and CheckMate 214 trial only enrolled a limited number of Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of tyrosine kinase inhibitors and immunotherapies has remarkably improved the survival of mRCC patients 1–12 . Randomized studies suggested the efficacy of first‐line nivolumab plus ipilimumab in patients belonging to the intermediate‐ and poor‐risk groups of the IMDC 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, molecular-targeted therapies have been generally used for treatment of mRCC. [1][2][3][4][5][6][7][8][9][10][11] As prognoses in mRCC have improved, more precise stratifications based on risk factors have been required. In the molecular-targeted therapy era, the IMDC risk classification is a standard riskbased stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, molecular‐targeted therapies have been generally used for treatment of mRCC . As prognoses in mRCC have improved, more precise stratifications based on risk factors have been required.…”
Section: Introductionmentioning
confidence: 99%